Efficient Algorithms for Approximating Particular Solutions of Elliptic Equations Using Chebyshev Polynomials (Communications in Computational Physics, 2007)
In this paper, we propose efficient algorithms for approximating particular solutions of second and fourth order elliptic equations. The approximation of the particular solution by a truncated series of Chebyshev polynomials and the satisfaction of the differential equation lead to upper triangular block systems, each block being an upper triangular system. These systems can be solved efficiently by standard techniques. Several numerical examples are presented for each case.